2014
DOI: 10.1103/physrevb.90.081104
|View full text |Cite
|
Sign up to set email alerts
|

Bond order and the role of ligand states in stripe-modulatedIrTe2

Abstract: The coupled electronic-structural modulations of the ligand states in IrTe2 have been studied by x-ray absorption spectroscopy (XAS) and resonant elastic x-ray scattering (REXS). Distinctive preedge structures are observed at the Te-M4,5 (3d → 5p) absorption edge, indicating the presence of a Te 5p -Ir 5d covalent state near the Fermi level. An enhancement of the REXS signal near the Te 3d → 5p resonance at the Q = (1/5, 0, −1/5) superlattice reflection is observed below the structural transition temperature T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 36 publications
4
32
0
Order By: Relevance
“…As stated previously, this is unexpected for a weakly bounded layered material [23][24][25]. Such ordering turns the high-temperature trigonal phase into the lowtemperature triclinic phase, with new unit cell vectors orientated in entirely different directions (the new c-axis is not perpendicular to a and b) [6,[26][27][28]. Further cooling causes the second structural transition at ~ 180 K, forming an 8×1×8 structural modulation with additional dimers in the unit cell [21,29].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…As stated previously, this is unexpected for a weakly bounded layered material [23][24][25]. Such ordering turns the high-temperature trigonal phase into the lowtemperature triclinic phase, with new unit cell vectors orientated in entirely different directions (the new c-axis is not perpendicular to a and b) [6,[26][27][28]. Further cooling causes the second structural transition at ~ 180 K, forming an 8×1×8 structural modulation with additional dimers in the unit cell [21,29].…”
Section: Introductionmentioning
confidence: 98%
“…However, STM does not directly probe the atomic structure. To date, the only surface structural measurement is via low energy electron diffraction (LEED), which showed a 5×1 reconstruction at 200 K and 1×1 character at 300 K [28]. Here, we report the temperature dependence of IrTe [34].…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of the experimental signal to these fluctuating quantities is material-dependent: in the cuprates it has been shown that the resonant scattering is predominantly controlled by variations in the energy shifts (i.e., a scalar field) [30,31], whereas in a different material, e.g. IrTe 2 , the RXS signal (at the Te-M absorption edge) was shown to be primarily associated to a combination of valence modulations and atomic displacements [46]. In presence of valence modulations or energy shifts (i.e., scalar operators), the fluctuating quantity is proportional to modulations in the electronic density ρ, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…tuations of this state possibly mediate superconductivity [29,46], tacitly implying similarity to unconventional SCs. Since most studies focus on the origin and mechanism of the phase transition [32,42,[45][46][47][48][49][50][51], the question whether the suppression of the low-T phase with chemical doping proceeds in a first or second order (QCP-like) manner is still not resolved.…”
Section: Introductionmentioning
confidence: 99%